404OA phase II single arm study of nivolumab and ipilimumab (Nivo/Ipi) in previously treated Classical Kaposi Sarcoma (CKS). (24th November 2019) - Zer, A; Icht, O; Jacobi, O; Fenig, E; Shamai, S; Merimsky, O; Shapira, R; Bernstine, H; Weitzen, R; Vornikova, O; Ben-Ami, E; Bar-Sela, G; et al.
Abstract: Background: CKS is an angioproliferative mesenchymal neoplasm causatively associated with human herpes virus 8 infection. Though recombinant IFNa is approved for treatment of AIDS-related KS, data is limited regarding the role of immune modulation. Based on favorable responses in viral-induced cancers, we hypothesized that CTLA-4 and PD-1 blockade can induce tumor regression in CKS. We present pre-planned interim analysis of a phase II study of Nivo/Ipi in previously treated (tx) progressive CKS. Methods: CKS pts with progressive disease after > 1 line of systemic tx and measurable disease by PET/CT and/or physical exam received nivolumab 240mg d1, 15, 28 and ipilimumab 1mg/kg d1 q42 days until progression or toxicity. The primary endpoint (EP) was overall response rate (ORR), secondary EP include 6-months progression free survival rate (PFS) and safety. Exploratory EP included PD-L1/MMR IHC, DNAseq (596 genes)/RNAseq (whole transcriptome) of tissue and matched blood to explore CKS genomic traits and IO correlates: TMB, MSI, dMMR, PD-L1, immune gene expression (PD1, CTLA4, etc) (Tempus Labs, Chicago, IL, USA). Results: Twelve patients were enrolled and evaluable between Apr2018-Jun2019 and 11 were evaluable for response. Median age 72 (61-81). At a mFU of 6 months ORR was 45% (4 pts PR, 1 pt CR, 6 pts SD). mPFS was not reached, 6-mo PFS rate was 91% (1 out of 11 patients had PD). The safety profile was as expected with three patients with G2 toxicity (1 ALT/AST increase, 1 asymptomatic lipase increase) and two patients with G3 toxicity (1 colitis, 1 asymptomatic lipase increase) . One SAE was reported (TIA considered not related to therapy) and treatment was discontinued in one pt (G2 LFT increase. maintaining CR 4 months after treatment discontinuation). Correlative results are available for four patients showing negative PDL1 IHC in all, low TMB, MS-S, but marked overexpression of CTLA4, PD1 and PDL1. Conclusions: The interim analysis in this prospectively designed phase II study of nivo/ipi demonstrate promising activity in progressive CKS, with 45% ORR and a 6mo PFS rate of 91%. Toxicity profile as expected in this class of drugs. Correlative studies are preliminary but warrants further investigation into immune gene expression profiles. Clinical trial identification: NCT03219671. Legal entity responsible for the study: The authors. Funding: BMS Rabin Medical Center. Disclosure: A. Zer: Honoraria (self), Research grant / Funding (institution): BMS; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: AZ. All other authors have declared no conflicts of interest.